Pengembangan Bahasa Anak Melalui Aktivitas Menulis - Misna Waroh; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
This article discusses strategies for developing language skills in early childhood through enjoyable writing activities that are appropriate for their developmental stages. The main aim of this research is to determine how activities such as writing in sand, recognizing letters, and forming simple words and syllables can effectively enhance children's fine motor skills and language literacy. By involving active participation from parents and educators, as well as employing a holistic and sustainable approach, it is expected that children will develop their communication, social, and cognitive abilities optimally. The study's results indicate that early verbal stimulation and writing activities are crucial in supporting language growth and preparing children for subsequent educational levels, thereby strengthening their literacy foundation and overall social-emotional development.